Spontaneous brain activity in healthy aging: An overview through fluctuations and regional homogeneity - Montalà-Flaquer, Marc; Cañete-Massé, Cristina; Vaqué-Alcázar, Lídia; Bartrés-Faz, David; Peró-Cebollero, Maribel; Guàrdia-Olmos, Joan (Frontiers in Aging Neuroscience, 2023)
Introduction: This study aims to explore whole-brain resting-state spontaneous brain activity using fractional amplitude of low-frequency fluctuation (fALFF) and regional homogeneity (ReHo) strategies to find differences among age groups within a population ranging from middle age to older adults. Methods: The sample comprised 112 healthy persons (M=68,80, SD=7,99) aged 48-89 who were split into 6 age groups (< 60, 60 to 64, 65 to 69, 70 to 74, 75 to 79, and ≥ 80). fALFF and ReHo analyses were performed and were correlated with the cognitive variables collected. Results: Increased activity was found using fALFF in the superior temporal gyrus and inferior frontal gyrus when comparing the first group and the fifth. Regarding ReHo analysis, Group 6 showed increased ReHo in the temporal lobe (hippocampus), right hippocampus, right caudate and right thalamus depending on the age group. Moreover, significant correlations between age and ReHo maps were found, meaning that the higher the age, the higher the regional synchronization. One of the two clusters found correlated positively with the vocabulary scale in the Wechsler adult intelligence scale. With regard to the correlation analyses with cognitive outcomes, there were negative significant relationship between some neuropsychological evaluations (Boston naming test and minimental score evaluation) and the signal of the significant clusters of ReHo. Conclusions: Both techniques have been shown to be valuable and usable tools for disentangling brain changes in activation in a very low interval of years in healthy aging.